Postnatal development of Mongolian gerbil female prostate: An immunohistochemical and 3D modeling study - Sanches, Bruno D.A.; Zani, Bruno C. [UNESP]; Maldarine, Juliana S. [UNESP]; Biancardi, Manoel F.; Santos, Fernanda C.A.; Góes, Rejane M. [UNESP]; Vilamaior, Patricia S.L. [UNESP]; Taboga, Sebastião R. [UNESP] (Wiley, 2016)
The development of the prostate in male rodents, which involves complex epithelial-mesenchymal interactions between the urogenital sinus epithelium (UGE) and the urogenital sinus mesenchyme (UGM), has been deeply studied. In females, however, this process is not very clear. In this study, the postnatal development of the prostate in female Mongolian gerbils employing three-dimensional (3D) reconstructions, histochemical, and immunohistochemical techniques was characterized. It was observed that prostatic branching and differentiation in females was induced by a single mesenchyme localized at a ventrolateral position, which was named as ventrolateral mesenchyme (VLM); furthermore, the canalization of solid buds began on the third postnatal day (P3) and the branching morphogenesis on P5. We observed secretions in the acini at the end of the first month, and, on P45, the acini were completely differentiated. The strong cell proliferation phase in the first week coincided with the mesenchymal expression of estrogen receptor 1 (ESR1). The expression of androgen receptor (AR) paralleled cell differentiation, and, on P30, immunolabelling with p63 was restricted to basal cells. This study serves as a baseline parameter for future research on disruptions that could affect the development of the female prostate. Microsc. Res. Tech. 79:438-446, 2016.
Keywords: Branching morphogenesis; Female prostate; Prostate development; Ventrolateral mesenchyme